2009
DOI: 10.1021/jp909380t
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study of Chlorophyll a Hydrates Formation in Aqueous Organic Solvents

Abstract: A theoretical analysis of chlorophyll a (Chla) hydration processes in aqueous organic solvents has been carried out by means of quantum chemistry calculations. A detailed knowledge of the thermodynamics of these processes is fundamental in order to better understand the organization of chlorophyll molecules in vivo, specifically the structure of chlorophyll pairs in photosystems I and II. In the present work, we assumed a Chla model in which the phytyl chain is replaced by a methyl group. Calculations were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 60 publications
3
27
0
1
Order By: Relevance
“…Ben Fredj and co-workers [7,8], have previously shown that BSSE contributions to ligation energies are significant. For large basis sets, the wisdom of this approach for hydrogen-bond and ligation interactions has been questioned as often the increase in the correlation energy with increasing basis exceeds the BSSE [41,42].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Ben Fredj and co-workers [7,8], have previously shown that BSSE contributions to ligation energies are significant. For large basis sets, the wisdom of this approach for hydrogen-bond and ligation interactions has been questioned as often the increase in the correlation energy with increasing basis exceeds the BSSE [41,42].…”
Section: Resultsmentioning
confidence: 99%
“…Following the basic methodology of Ben Fredj and RuizLópez [8], the ligation free energies in solution of Chl-a with explicit solvent molecules were calculated using a composite approach. Geometries for Chl-a complexed in the gas phase with various ligands in axial and diaxial coordination were optimised using Gaussian 09 Revision D.01 [31].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations